DINAMIKA INOVASI KURIKULUM PAI BERBASIS GAMIFIED-PROBLEM BASED LEARNING: SOLUSI TEORETIS MENGHADAPI RESISTENSI BELAJAR DI ERA DISRUPSI - Rani Safitri; Pely Welgya; Suci Adillah; Dita Haryani; Veoreta Vitriana; Febri Trifanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the dynamics of Islamic Education (PAI) curriculum innovation based on Gamified-Problem Based Learning (GPBL) as a theoretical solution to overcome learning resistance in the era of disruption. The method used is qualitative research with a library research approach, supported by empirical data through observation, interviews, and documentation involving 30 fifth-grade students, 4 PAI teachers, and 1 principal at SD Islam Plus Daaruth Thullab 02 Koto Salak. The results show a significant improvement after the implementation of GPBL, with student activeness in asking questions increasing from 26% to 73%, learning focus from 67% to 80%, and learning interest from 33% to 83%, while passive students decreased from 60% to 20%. These findings indicate that GPBL is effective in creating interactive, contextual, and engaging learning. The impact of this approach is the enhancement of student motivation, engagement, and the overall quality of PAI learning.